2014
DOI: 10.1016/j.biomaterials.2013.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Stable corneal regeneration four years after implantation of a cell-free recombinant human collagen scaffold

Abstract: We developed cell-free implants, comprising carbodiimide crosslinked recombinant human collagen (RHC), to enable corneal regeneration by endogenous cell recruitment, to address the worldwide shortage of donor corneas. Patients were grafted with RHC implants. Over four years, the regenerated neo-corneas were stably integrated without rejection, without the long immunosuppression regime needed by donor cornea patients. There was no recruitment of inflammatory dendritic cells into the implant area, whereas, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
212
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(220 citation statements)
references
References 23 publications
3
212
1
2
Order By: Relevance
“…Visual acuity among patients was similar to normal cornea function across the study (Fagerholm et al, 2010). Furthermore, sufficient nerve regeneration and stromal repopulation was found in patients over a 4-year period following the original study (Fagerholm et al, 2014). The long-term safety and efficacy denoted in these studies is promising for future applications.…”
Section: Corneal Regeneration or Replacement Using Bioactive Materialsmentioning
confidence: 61%
“…Visual acuity among patients was similar to normal cornea function across the study (Fagerholm et al, 2010). Furthermore, sufficient nerve regeneration and stromal repopulation was found in patients over a 4-year period following the original study (Fagerholm et al, 2014). The long-term safety and efficacy denoted in these studies is promising for future applications.…”
Section: Corneal Regeneration or Replacement Using Bioactive Materialsmentioning
confidence: 61%
“…In a 4 year follow up of ten patients using this technique for partial thickness grafts it is reported that these implants have integrated and are stable (Figure 6). [42] More recently, a modification to these scaffolds has incorporated synthetic phospholipids to inhibit neovascularization for application in more complex corneal disorders. [43] Collagen type 1 (equine) has also been crosslinked using riboflavin and ultraviolet A (UVA), similar to the clinical treatment for keratoconus, and this has been shown to reduce the degradation of the collagen in vitro and after implantation intrastromally in rabbits.…”
Section: Stromamentioning
confidence: 99%
“…Reproduced with permission. [42] Copyright 2014, Elsevier. cells in culture on a substrate so that one donor cornea could be used to treat more than one patient.…”
Section: Endotheliummentioning
confidence: 99%
“…86 A 4-year follow-up showed the construct stably integrated without rejection, whereas future steps are focused on improving visual acuity based on materials with better shape retention. 87 …”
Section: Full-thickness Cornea Equivalentmentioning
confidence: 99%